The Application of Playing in Early Childhood Education Based on Piaget’s Way of Thinking - Mauluddia, Yulia; Solehuddin, M. (Universitas Islam Negeri Raden Intan Lampung, 2023)
Childhood is identic with playing, and children are also said to be Homo Ludens or creatures of play. The Indonesian government is promoting criteria emphasizing play as a learning process. In addition, an emancipated curriculum means that children are given the opportunity for freedom of choice and activities so that students can build their knowledge. This policy contributes to Piaget's concept of thinking, which sees how children learn by constructing their knowledge. This study looks at the application of play in early childhood education based on Piaget's way of thinking. This study uses a systematic literature review research method. The results of this study discuss how Piaget views the concept of play in early childhood. The update of this article from the previous article is that it will explain early childhood play activities more precisely according to Piaget's views. Piaget asserts that knowledge development occurs through imagination in new experiences, which actively builds and modifies prior knowledge, and play is the primary medium in which this process occurs. The results of this paper are useful for educators and parents who know better how play can provide an unconscious learning process in children.